Basin Model of Total Dissolved Salts Transformation in Water of a Small River (the Kirgizka River, Tomsk, Russia); IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Savichev O. G. Oleg Gennadievich (Hydrogeochemistry and Hydrogeoecology, 2016)
Title screen